WEA Plan for Education, 1942 (1942)
1942 1939-1945 "WEA Plan for Education, 1942" [HFR0132], 1942 The Plan for Education, published by the Workers' Educational Association in 1942, outlines their proposals for the restructuring of educational policy after the war and includes a special appendix on agriculture and rural education. One of its key principles is " a common school system in which distinctions and privileges no longer play any part" and it also covers nursery and higher education, lifelong adult education and child labour.